2018
DOI: 10.1111/jocs.13713
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between intraoperative serum lactate and hemoglobin levels on postoperative renal function in patients undergoing elective cardiac surgery

Abstract: In this series, 15% of patients who underwent elective cardiopulmonary bypass developed transient acute renal dysfunction. High lactate levels and low hemoglobin levels during cardiopulmonary bypass were associated with an increased risk of kidney injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
0
11
1
Order By: Relevance
“…This is similar to other studies in septic patients and patients undergoing cardiac surgery in whom elevated lactic acid levels were associated with acute kidney injury. 23,24 We found that both exogenous catecholamines and longer CPB were associated with higher lactic acid levels. Both of these factors have previously been associated with postoperative acute kidney injury in other surgical groups.…”
Section: Commentmentioning
confidence: 79%
“…This is similar to other studies in septic patients and patients undergoing cardiac surgery in whom elevated lactic acid levels were associated with acute kidney injury. 23,24 We found that both exogenous catecholamines and longer CPB were associated with higher lactic acid levels. Both of these factors have previously been associated with postoperative acute kidney injury in other surgical groups.…”
Section: Commentmentioning
confidence: 79%
“…Blood lactate can reflect stress intensity and perfusion of organ and tissue. Some recent studies have reported that the level of blood lactate is significantly correlated with hospitalization duration, incidence of complications and risk of death 20,21 . Our trial showed lower lactate and more urine in the patients of TAP + LMA group than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers involved in a Spanish multicenter cohort study [112] reported that patients with a postoperative hemoglobin (Hb) level <19 g/dL tended to experience CSA-AKI (OR 1.41) after adjusting for intraoperative red blood cell transfusion. An Hb drop after cardiac surgery also contributed to a prolonged hospital length of stay [113]. In addition, iron metabolism may play a role in the pathophysiology of kidney injury.…”
Section: Other Biomarkersmentioning
confidence: 99%